(untitled) (Journal of Asian Development Studies, 2025)
Written corrective feedback plays a vital role in developing L2 writing among ESL learners, and engagement is a tool that helps students achieve error-free writing. This research shows that written corrective feedback is directly proportional to student engagement, which depends on the extent to which students follow the teacher’s comments. This study uses a mixed-methods approach, combining experimental and qualitative research to calculate results. However, some drift persists in identifying the link between student engagement with feedback and the learning outcomes it yields. The population of this study comprises higher secondary school students, and the study examines how they engage with written corrective feedback behaviorally, affectively, and cognitively. Data were collected through tests and questionnaires administered to higher secondary students, and interviews were conducted with five haphazardly selected students. The results showed that variables are to some extent linked with written corrective feedback. This study is complex, in which students’ engagement with corrective feedback is calculated across three dimensions of student engagement.